2023
DOI: 10.3390/ijerph20032312
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cannabinoids in Biological Specimens: An Update

Abstract: Cannabinoids are still the most consumed drugs of abuse worldwide. Despite being considered less harmful to human health, particularly if compared with opiates or cocaine, cannabis consumption has important medico-legal and public health consequences. For this reason, the development and optimization of sensitive analytical methods that allow the determination of these compounds in different biological specimens is important, involving relevant efforts from laboratories. This paper will discuss cannabis consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 117 publications
(242 reference statements)
2
14
0
Order By: Relevance
“…This study revealed that urine, a non-blood bodily fluid, could be utilized for the analysis of cannabinoid metabolites [21]. Despite examining almost four times more cases than the Saenz et al [13] study, a lower proportion of urine specimens tested positive for THC-OH and THC.…”
Section: Discussionmentioning
confidence: 75%
“…This study revealed that urine, a non-blood bodily fluid, could be utilized for the analysis of cannabinoid metabolites [21]. Despite examining almost four times more cases than the Saenz et al [13] study, a lower proportion of urine specimens tested positive for THC-OH and THC.…”
Section: Discussionmentioning
confidence: 75%
“…However, this technique is limited by several factors such as temperature change, antibody binding constants, diffusion rates, device orientation, and lack of specificity. 15…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique is limited by several factors such as temperature change, antibody binding constants, diffusion rates, device orientation, and lack of specificity. 15 In the past decades, electrochemical techniques have been explored for the detection of THC in various bodily fluids. Many researchers have used screen printed electrodes and glassy carbon electrode platforms with mediator chemistry for THC detection by square wave voltammetry and chronoamperometric techniques.…”
Section: Introductionmentioning
confidence: 99%
“…39 Improper selection of the extraction method may lead to degradation of THC and its conversion into a chemical that may yield a false positive/negative result. 40 Advanced available extraction methodologies have also been employed to increase the yield of THC. 41 These methodologies involve ultrasonic-assisted extraction (UAE), 42 microwave-assisted extraction (MAE), supercritical-fluid extraction (SFE), matrix solid-phase dispersion (MSPD), pressurized fluid extraction (PFE), and micropulverized extraction.…”
Section: Procedures For Sample Preparationsmentioning
confidence: 99%